2017
DOI: 10.31018/jans.v9i3.1439
|View full text |Cite
|
Sign up to set email alerts
|

Screening for pod shattering in mutant population of mungbean (Vigna radiata (L.) Wilczek)

Abstract: Mungbean, (Vigna radiata (L.) Wilczek) occupies a unique position in Indian agriculture and has been grown under various agro-ecological conditions. It is cultivated in 1.61mha with production of 3.38MT and productivity of 474kg/ha in India. Mungbean pods are thin and brittle when dry, so shattering is a major problem. The loss of seeds by pod dehiscence is one of the major reasons for low yield in mungbean; thus, reducing the frequency of pod dehiscence is an important objective in mungbean breeding. Induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In other crops, such as mungbean, it also showed that the indeterminate flowering habit of this crop contributes to the spread of flowering and pod maturity over the entire reproductive phase on a single plant. As a result, pods that develop at the earliest flower may shatter before 100% pod maturity (Vairam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other crops, such as mungbean, it also showed that the indeterminate flowering habit of this crop contributes to the spread of flowering and pod maturity over the entire reproductive phase on a single plant. As a result, pods that develop at the earliest flower may shatter before 100% pod maturity (Vairam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…All of these varieties had a significantly lower seed weight compared to DX-208. Although there is ongoing research with mungbean germplasm focussed on the non-shattering trait (Nirmalbharati et al, 2016;Vairam, 2017), there appears to be no published research on pod-shattering characteristics of commercialized mungbean varieties. The Australian mungbean improvement program selects for the non-shattering trait (Douglas, 2017).…”
Section: Experiments In the Wet Season 2021mentioning
confidence: 99%
“…Pod-shattering, as an evolved seed dispersal mechanism, is an important cause of yield loss in crops such as mungbean, which are still in the process of domestication (Nirmalbharati & Sumangala, 2016). Although mungbean germplasm is subject to various studies such as molecular diversity analysis (Nirmalbharati & Sumangala, 2016), and screening for pod shattering in mutant populations (Vairam et al, 2017), no useful published comparisons can be found on pod-shattering in commercial mungbean varieties. In 2018, three Thai and four Vietnamese varieties were evaluated at two sites in Battambang (Campbell-Ross et al, 2019) but rejected for evaluation in this study because they had lower seed weights compared to DX-208.…”
Section: Introductionmentioning
confidence: 99%
“…In mungbean, it was reported that the indeterminate flowering habit leads to a spread of flowering and pod maturity on a single plant over the entire reproductive phase. Consequently, pods that develop at the earliest flower may shatter prior to 100% pod maturity (Vairam et al 2017).…”
Section: Pod Positions On the Plant Associated With Pod Shattering Resistance In Soybean Genotypesmentioning
confidence: 99%
“…Krisnawati et al (2019a) have successfully selected a total of 104 very resistant lines in the 591 F 5 segregating population of soybean derived from crosses of the resistant parent. A screening for pod shattering in the mutant populations of green-gram obtained nine tolerant mutants in the M 3 generation (Vairam et al 2017). In the molecular approach, Thakare et al (2017) have found two markers that could be utilized in the marker assisted for pod shattering resistance.…”
Section: Introductionmentioning
confidence: 99%